Investment climate around the world : voices of the firms from the World Business Environment Survey - Batra, Geeta; Stone, Andrew H. W., 1958-; Kaufmann, Daniel, 1951- (Washington, D.C. : World Bank, 2003)
This book present the core WBES questionnaire and survey findings, and confirms the significance of key country conditions on the firm performance and behavior. The finding provide a basis for regional comparison, but suggest the need for caution when averaging across categories, especially in light of country conditions that can significantly affect firm-level sales and investment.
CD-ROM provides the complete World Business Environment Survey (WBES), an initiative led by the World Bank Group, core database, an interactive tool that users to configure and analyze graphs, and links to Web-based analytical tools.
Includes bibliographical references (p. 151-154).
oif 23/03/15
Loan
Keywords: Globalization; Investments, Foreign; International business enterprises